Islamic peace ethics: legitimate and illegitimate violence in contemporary islamic thought - Shadi, Heydar (Studien zur Friedensethik, 2017)
Introduction -- I. Methodology and theory -- Some methodological remarks on islamic peace ethics / Heydar Shadi -- Is it essentialism to claim that some religions foster violence -- and some do not? / Dirk Ansorge -- Discussing islamic peace ethics : conceptual considerations of the normative / Sybille Reinke de Buitrago -- Peace and violence in Islam : philosophical issues / Oliver Leaman -- II. Jus ad bellum -- A. Sunni -- Violence in contemporary indonesian islamist scholarship : Habib Rizieq Syihab and 'enjoining good and forbidding evil' / Asfa Widiyanto -- Citizenship as inclusion and exclusion : arguments against religious violence from contemporary Pakistan / Najia Mukhtar -- Blessed boundaries : the limits of Sunnah to legitimize violence / Charles M. Ramsey -- Islamic views of peace and conflict among Russia's Muslims / Simona E. Merati -- B. Shi'ah -- A Qur'anic revision of offensive war with emphasis on the views of the late Ayatollah Khoei / Yahya Sabbaghchi -- The rhetoric of power in Muhammad Husayn Fadlallah's al-Islam wa-mantiq al-quwwa / Bianka Speidl -- C. Sufi -- Jawdat Sa'id and the Muslim philosophy of peace / Abdessamad Belhaj -- III. Jus in bello -- Lying in war : different ethical justifications / Seyed Hassan Eslami Ardakani -- Short biographies of the authors -- The institute of theology and peace (ithf)